Locally advanced adenocarcinoma of the cervix on uterus didelphys: a case report - Cordoba, Abel; Escande, Alexandre; Comte, Pauline; Fumagalli, Ingrid; Bresson, Lucie; Mubiayi, Ndaye; Lartigau, Eric (Journal of Contemporary Brachytherapy, 2017)
In November 2013, a woman with Herlyn-Werner-Wunderlich (HWW) syndrome was diagnosed with a locally advanced left cervical adenocarcinoma. The patient’s malformation consisted of two uteri with two cervixes, a obstructed vagina, and a left renal agenesis. Classification FIGO: stage IIIa because of infiltration of the inferior third of the vagina wall. Locoregional management comprised an infrarenal lateral aortic lymphadenectomy followed by concomitant radio-chemotherapy to the pelvic (inguinal, pelvic, and infrarenal para aortic nodes) volumes. A total of 50.4 Gy were delivered (1.8 Gy/fraction/day) to the node (inguinal, pelvic, and aortic infrarenal) and pelvic volume; a concomitant boost to the primary cervical tumor and macroscopic nodes to 59.92 Gy (2.14 Gy/fraction/day) was performed. 20 Gy were delivered with intracavitary brachytherapy boost with mold technique and a pulsed-dose-rate technique due to the rarity of this uterine malformation. After 30 months of follow-up, there was no evidence of locoregional or distant recurrence.